PENGARUH CITRA MEREK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN TAS WANITA DI KOTA DEPOK - Diajeng Wurikinasih; Instianti Elyana (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
The fashion industry has undergone substantial growth driven by evolving consumer preferences, wherein buyers increasingly prioritize not only product functionality but also aesthetic design and a strong brand image. This research seeks to examine how perceptions of brand identity and structural attributes of the product shape consumer buying behavior. decisions for women’s handbags in Depok City, offering scholarly contribution by assessing these variables both individually and collectively. The research employed a quantitative approach using non-probability targeted sampling, where information was obtained from individuals aligned with the predetermined qualifications related to handbag purchases. The findings reveal that 59.5% of purchasing decisions are explained by brand image and product design, with brand image contributing 3.496 and product design contributing 4.452, indicating that product design serves as the most influential determinant. These results underscore the importance for industry practitioners to prioritize design innovation aligned with prevailing market trends while simultaneously strengthening brand image to enhance consumer purchase decisions.